Baseline Parameters in Untreated Ovarian and Breast (Symptomatic and Asymptomatic Covid-19) Cancer Patients (Medical Forum Monthly, 2022)
Objective: To evaluate the effect of covid-19 on CBC, LFT’s, RFT’s and TMR’s in cancer patients.Study Design: A prospective studyPlace and Duration of Study: This study was conducted at Multan Institute of Nuclear Medicine and Radiotherapy (MINAR) from April 2019 to December 2020.Materials and Methods: This study was performed on 3772 untreated cancer patients (includes bladder, bone, brain, breast, colon, larynx, leukemia, liver, lung, ovary and other cancer types with age ranging from 8-87 years (49.59±15.27) of 2019 and 2020 (50% of COVID attack) at MINAR hospital, Multan. Chi-square Mann Whitney, Independent T- test and Spearman correlation analysis were performed to calculate results.Results: The incidence of bone cancer (p value-0.02), brain cancer (p value-0.03), breast cancer (p value-0.00001) liver cancer (p value-0.006), and ovarian cancer (p value-0.0001) was higher in 2020 patients. All cancers, data indicated that Creatinine (p=0.004) and CA 125(p=0.04) were in higher ranges in COVID 19 cancer patients. There observed significant change in creatinine levels of breast (p=0.02) and ovarian cancer patients (p=0.04) and also higher level of CA-125(p=0.04) was indicated in ovarian cancer patients along with covid-19. There observed strongly significant positive association of CA- 125 with creatinine (r=0.34, p=0.02), and CEA with Bilirubin Total(r=0.57, p=0.04) in ovarian cancer. MCV (p=0.00), HGB (p=0.01), HCT (p=0.04), MCH (p=0.001), and MCHC (p=0.02) were decreased in breast cancer patients. CA-125 showed a strongly significant negative association with LY %( r= -0.305, p=0.03) and MO %( r= -0.299, p=0.049) in ovarian cancer.Conclusion: Our findings suggest that incidence of ovarian cancer and breast cancer was very high during COVID pandemic attack. Association of CA 125 with creatinine in breast cancer and with LY% and MO% in ovarian cancer serve as the prognostic factor during viral attack. MCV and Creatinine are diagnostic factors in both cancers.